Reinforcing the Position of Waqf in the Islamic Financial Ecosystem in Indonesia - Nasution, Lokot Zein; Aris, Diba Anggraini; Suryadinata, M; Nurhayanti, Yanti (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2021)
Abstract. This study aims to evaluate the position of waqf in the Islamic financial ecosystem in Indonesia. This study adopts an evaluative descriptive research method by distributing a set of questionnaires to expert informants which include Wakif, Nazir, Indonesian Waqf Agency, the Ministry of Religious Affairs, the Ministry of Finance, third parties that collaborate with Nazir, and other relevant parties. The result shows that Waqf can set religious norms and provide guidelines for economic activities. The most strategic instruments to apply in the Islamic financial markets include Zakat, Infaq, Sadaqah, and waqf (ZISWAF). The four instruments have been considered to increase prosperity and manage income distribution in order to reduce income inequality. Waqf, in particular, plays an important role in building and supporting economic development in the country, especially through the socio-economic dimension. As one of the instruments to distribute wealth in Islam, it is able to produce high-quality development. However, there are two fundamental issues regarding the national waqf, institutional and market problems. The national waqf requires institutional support and market order to build the established Islamic finansical ecosystem.Keywords: Islamic Finance, Productive Waqf, Waqf Ecosystem Abstrak. Penelitian ini bertujuan untuk mengevaluasi posisi wakaf dalam ekosistem keuangan syariah di Indonesia. Penelitian ini menggunakan metode penelitian deskriptif evaluatif dengan mendistribusikan kuesioner kepada informan ahli, meliputi wakif, nazhir, Badan Wakaf Indonesia, Kementerian Agama, Kementerian Keuangan, dan pihak terkait lainnya. Hasilnya menunjukkan bahwa wakaf memiliki kekuatan untuk menetapkan norma-norma agama dan memberikan pedoman untuk kegiatan ekonomi. Instrumen yang paling strategis untuk diterapkan di pasar keuangan Islam termasuk Zakat, Infaq, Sadaqah, dan wakaf (ZISWAF). Keempat instrumen tersebut telah dipertimbangkan untuk meningkatkan kemakmuran dan mengelola distribusi pendapatan guna mengurangi ketimpangan pendapatan. Wakaf, khususnya, memainkan peran penting dalam membangun dan mendukung pembangunan ekonomi di tanah air, terutama melalui dimensi sosial ekonomi. Sebagai salah satu instrumen untuk mendistribusikan kekayaan dalam Islam, wakaf mampu menghasilkan pembangunan berkualitas tinggi. Namun, ada dua isu mendasar mengenai masalah wakaf nasional, kelembagaan dan pasar. Wakaf nasional membutuhkan dukungan kelembagaan dan ketertiban pasar untuk membangun ekosistem keuangan Islam yang mapan.Kata kunci: Keuangan Syariah, Waqf Produktif, Waqf Ekosistem